Chatbots and robots: a framework for the self-management of occupational stress - Akihiro Yorita; Simon Egerton; Carina Chan; Naoyuki Kubota (ROBOMECH Journal, 2023)
Abstract We have developed a stress management framework aimed at helping healthcare professionals manage occupational stress. A chatbot is used to gather pertinent information from a user through regular conversation which is processed via a fuzzy inference model to derive their level of occupational Comprehensibility, Manageability, Meaningful and overall occupational Sense of Coherence (SOC). This analysis feeds into a Peer Support model which selects the best intervention aimed at enhancing a user’s stress-coping abilities and reducing their levels of occupational stress. A trial has been conducted with working adults, and the results were examined using a questionnaire supported by Technology Acceptance Model, which showed that the chatbot could recognize the user's SOC, but left a challenge: few users wanted to continue using it in their daily lives.